The Moon as a Cosmic-Ray Spectrometer: Prospects for MeV Gamma-Ray Observations - Tatsuki Fujiwara; Ellis R. Owen; Yoshiyuki Inoue; Manel Errando; Kohei Fukuda; Kazuhiro Nakazawa; Hirokazu Odaka; Keigo Okuma; Kentaro Terada; Naomi Tsuji; Yasunobu Uchiyama; Hiroki Yoneda; et al. (The Astrophysical Journal, 2025)
The Moon is the closest celestial gamma-ray emitting object. Its gamma-ray emission arises from interactions between Galactic cosmic rays (CRs) and the lunar surface. While the lunar GeV gamma-ray spectrum is dominated by a continuum from hadronic decay processes, the MeV emission exhibits both continuum and distinctive spectral lines from nuclear de-excitation and radioactive decay processes. Using Geant4 Monte Carlo particle simulations, we model the lunar gamma-ray spectrum. Our results demonstrate its consistency with Fermi-Large Area Telescope observations, and predict that next-generation MeV gamma-ray instruments will detect both the lunar MeV continuum and several key spectral line features, notably the 1.779 MeV line from ^28 Si de-excitation enhanced by the lunar surface composition, the e ^+ e ^− annihilation line, and radioactive decay lines from ^22 Na ( τ  ≈ 3.75 yr) and long-lived ^26 Al ( τ  ≈ 1 Myr). These gamma-ray lines are sensitive to CRs with energies ≲1 GeV nuc ^−1 , offering unique temporal probes of CR activity over different timescales. Observations of the lunar MeV gamma-ray spectrum will therefore open a new window to study the current irradiation of the solar-terrestrial environment by low-energy CRs and its long-term temporal evolution.